Pharmacological AMP kinase activators target the nucleolar organization and control cell proliferation. - Mohamed Kodiha (Public Library of Science (PLoS), 2014)
Aims Phenformin, resveratrol and AICAR stimulate the energy sensor 5'-AMP activated kinase (AMPK) and inhibit the first step of ribosome biogenesis, de novo RNA synthesis in nucleoli. Nucleolar activities are relevant to human health, because ribosome production is crucial to the development of diabetic complications. Although the function of nucleoli relies on their organization, the impact of AMPK activators on nucleolar structures is not known. Here, we addressed this question by examining four nucleolar proteins that are essential for ribosome biogenesis. Methods Kidney cells were selected as model system, because diabetic nephropathy is one of the complications associated with diabetes mellitus. To determine the impact of pharmacological agents on nucleoli, we focused on the subcellular and subnuclear distribution of B23/nucleophosmin, fibrillarin, nucleolin and RPA194. This was achieved by quantitative confocal microscopy at the single-cell level in combination with cell fractionation and quantitative Western blotting. Results AMPK activators induced the re-organization of nucleoli, which was accompanied by changes in cell proliferation. Among the compounds tested, phenformin and resveratrol had the most pronounced impact on nucleolar organization. For B23, fibrillarin, nucleolin and RPA194, both agents (i) altered the nucleocytoplasmic distribution and nucleolar association and (ii) reduced significantly the retention in the nucleus. (iii) Phenformin and resveratrol also increased significantly the total concentration of B23 and nucleolin. Conclusions AMPK activators have unique effects on the subcellular localization, nuclear retention and abundance of nucleolar proteins. We propose that the combination of these events inhibits de novo ribosomal RNA synthesis and modulates cell proliferation. Our studies identified nucleolin as a target that is especially sensitive to pharmacological AMPK activators. Because of its response to pharmacological agents, nucleolin represents a potential biomarker for the development of drugs that diminish diabetic renal hypertrophy.